2015
DOI: 10.1007/s10995-015-1773-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior Patterns Before and During Pregnancy in a Multi-ethnic Sample of Asian Women in Singapore

Abstract: Participants substantially reduced PA and increased SB by 26-28 weeks of pregnancy. Further research is needed to better understand determinants of change in PA and SB and develop effective health promotion strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
80
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 46 publications
14
80
2
2
Order By: Relevance
“…The amount of time spent in sedentary behaviours was estimated in 8 studies using either objective [8–12, 30, 38, 44] or non-objective methods [42] (Table 3). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of time spent in sedentary behaviours was estimated in 8 studies using either objective [8–12, 30, 38, 44] or non-objective methods [42] (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…Of these studies 1 declared that sleeping was included [9], 2 stated that sleep time was not considered [8, 11], and the rest did not declare anything regarding sleep [10, 12, 44]. Meanwhile the study which assessed using a questionnaire found that women spent 2.4 h per day watching television and the mean of total sitting time was 8.6 h per day [42] (Table 3). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations